2023
DOI: 10.3389/fvets.2022.1039032
|View full text |Cite
|
Sign up to set email alerts
|

Adding a polyphenol-rich fiber bundle to food impacts the gastrointestinal microbiome and metabolome in dogs

Abstract: IntroductionPet foods fortified with fermentable fibers are often indicated for dogs with gastrointestinal conditions to improve gut health through the production of beneficial post-biotics by the pet's microbiome.MethodsTo evaluate the therapeutic underpinnings of pre-biotic fiber enrichment, we compared the fecal microbiome, the fecal metabolome, and the serum metabolome of 39 adult dogs with well-managed chronic gastroenteritis/enteritis (CGE) and healthy matched controls. The foods tested included a test f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…Fecal moisture decreased linearly and fecal score increased linearly throughout the treatment period, suggesting improved GI health and stool quality throughout the study. This aligns with previous work in adult dogs showing that food fortified with the prebiotic fiber blend has beneficial effects on stool quality, both over time and in comparison to dogs fed a control food without the fiber blend ( 24 , 25 , 27 ). The decline in fecal moisture in the puppies throughout the study duration is also indicative of reduced fecal water loss, which indicates a potential association between the test food and body water retention.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Fecal moisture decreased linearly and fecal score increased linearly throughout the treatment period, suggesting improved GI health and stool quality throughout the study. This aligns with previous work in adult dogs showing that food fortified with the prebiotic fiber blend has beneficial effects on stool quality, both over time and in comparison to dogs fed a control food without the fiber blend ( 24 , 25 , 27 ). The decline in fecal moisture in the puppies throughout the study duration is also indicative of reduced fecal water loss, which indicates a potential association between the test food and body water retention.…”
Section: Discussionsupporting
confidence: 90%
“…An increase in BCFA production has been associated with higher levels of harmful compounds, including uremic toxins ( 27 ). Previous studies have found a decrease in BCFAs in dogs with chronic large bowel diarrhea and an increase in some individual SCFAs in both healthy adult dogs and adult dogs with chronic large bowel diarrhea when fed a food fortified with this prebiotic fiber blend ( 24 , 25 , 27 ). The results of this present study are aligned with findings seen in adult dogs, and indicate a shift in the gut environment of puppies fed this novel prebiotic towards one that is more favorable for saccharolytic fermentation, which is associated with favorable GI function and overall health ( 27 , 34 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, it is important to note that the analysis of the microbiome by 16srRNA sequencing methods alone may not portray the full potential benefits of probiotics since these techniques merely detect the numbers of species in the samples analyzed. These analyses therefore neglect to investigate the functional effects of probiotics in the intestine, which can be better assessed through comprehensive fecal and serum metabolomics, which represent changes in the metabolic activity of the microbes, of the gut, and of the host, respectively [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the rising concerns regarding anthelmintic drug resistance in companion animals, and a wider appreciation of the drawbacks of using chemotherapy to treat infections in animals (e.g., chemical residues in the environment), there has been an increasing interest in the development of functional food components (e.g., phytochemicals) in pet foods that may improve gut health [30,31]. To this end, in the present study we explored whether natural plant-derived compounds may represent a novel treatment option for U. stenocephala.…”
Section: Introductionmentioning
confidence: 99%